(untitled) (Eurasian Scientific Herald, 2022)
In this article, the requirements for the officer corps are increasing, the current officer is not only a person with limited knowledge in a particular area, but also a person with a deep intellectual potential, a broad outlook, highly cultured and spiritual, self-cognizing, personal on the example of the idea of being a capable and skillful teacher who can educate and train his subordinates.